Hemato-biochemical and hormonal profiles in post-partum water buffaloes (Bubalus bubalis) - Kumar, Sunil (Vet World, 2015)
AIM: The objective of the present study was to compare serum as well as follicular fluid (FF) biochemical and hormonal profiles along with hematological parameters in postpartum estrus, anestrus, and cystic buffaloes. MATERIALS AND METHODS: Postpartum buffaloes were selected in three different groups (within 40-60 days of parturition at estrus-Group-I, postpartum >90 days at anestrum-Group-II, and postpartum cystic buffaloes in Group III). The animals selected were examined for follicular wave dynamics by routine trans-rectal ultrasonography and FF was collected by transvaginal ultrasound-guided ovum pick up technique. All hematological and biochemical parameters were analyzed by automatic analyzers while hormonal profiles analyzed by commercially available ELISA kits. RESULTS: In the present investigation, estrum and anestrum animal differ significantly in hemoglobin levels. Serum estradiol differs significantly in estrus and anestrus while no significant difference in progesterone concentration was noted among all three stages. The results of our study suggest that significant higher increase in total protein (TP), calcium and glucose values in estrum while urea, aspartate aminotransferase, alanine aminotransferase, lactate dehydrogenase significantly higher in anestrum animals. CONCLUSION: The conclusion of the present study is that TP and albumin, calcium, urea, glucose affects oocyte development and quality.